PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Tiyas Suci Istikomah; Suprihatmi Sri Wardiningsih; Retno Susanti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the effect of product quality and price on customer satisfaction, the effect of product quality, price and customer satisfaction on customer loyalty, the effect of product quality and price on customer loyalty with satisfaction as a mediating variable. The population of this research is the customer of Warung Tengkleng Solo Bu Jito Dlidir with a sample of 100 respondents. Data collection techniques used questionnaire. Data analysis techniques used the t test, F test, coefficient of determination and multiple test. The results showed that product quality and price has significant effect on customer satisfaction. Product quality, price and customer satisfaction has a significant effect on customer loyalty. Customer satisfaction mediates the effect of product quality and price on customer loyalty.